2021
DOI: 10.3390/app112411607
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Storage Effects in the Recirculation Zone Based on the Junction Angle of Channel Confluence

Abstract: In this study, numerical simulations using the Environmental Fluid Dynamics Code model were conducted to elucidate the effects of flow structures in the recirculation zone on solute storage based on the junction angle. Numerical simulations were performed at a junction angle of 30° to 90° with a momentum flux ratio of 1.62. The simulation results revealed that an increase in the junction angle caused the recirculation zone length and width to increase and strengthened the development of helical motion. The hel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…The recirculation zone size is known to be enlarged with the increase in the momentum ratio and confluence angle from experimental and simulation results [9,31,32,34]. The enlarged recirculation zone drives to increase the retention time of the trapped solute cloud, and thus, the pollutant is trapped and accumulates at the inner bank at a larger confluence angle (Figure 10b,c).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The recirculation zone size is known to be enlarged with the increase in the momentum ratio and confluence angle from experimental and simulation results [9,31,32,34]. The enlarged recirculation zone drives to increase the retention time of the trapped solute cloud, and thus, the pollutant is trapped and accumulates at the inner bank at a larger confluence angle (Figure 10b,c).…”
Section: Discussionmentioning
confidence: 93%
“…Thus, the channel width (W) is 10 m, and the width-to-depth ratio is about 3.0. The mesh size was referred to in the study by Shin et al [9], in which the grid sensitivity was checked for the 90 • confluence channel using EFDC by comparisons to the measurements by Weber et al [27]. The study suggested the grid size as ∆x < W/20 for grid independency and computational efficiency.…”
Section: Simulation Conditionsmentioning
confidence: 99%
See 3 more Smart Citations